BERPERAN AKTIF DALAM MEMPERBAIKI BACAAN AL-QUR’AN ANAK-ANAK DI NAGARI PALOKAN INDERAPURA - Lestari, Puja Dinda; samin, Samin; Fadil, Marjan; Zebua, Ali Marzuki (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
Learning to read the Koran well and correctly is an obligation for every Muslim. Because the Al-Qur'an is a form of worship that brings oneself closer to the Creator, such as reading, reciting and memorizing it. This requires that a Muslim must be correct in choosing a teacher and method in learning to read the Al-Qur'an, because if he pronounces it wrong, it will change the meaning of the Al-Qur'an. There are several things that a person needs to learn in order to improve the quality of reading the Al-Qur'an, including improving the reading of the Al-Qur'an, starting from Tajwid Science, Makhorijul Letters and the Characteristics of 1 Letter.